2008
DOI: 10.20452/pamw.298
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes care and self-monitoring of type 2 diabetic patients in a rural district of West-Pomeranian Province

Abstract: Introduction. Few surveys conducted in diabetic patients from rural regions show that in these subjects monitoring of diabetes is worse than in patients from urban areas. Objectives. To assess methods of diabetes care provided for type 2 diabetic patients residing in a rural region and methods of the patient self-monitoring of glycemia, blood pressure and foot self-care. Patients and methods. The survey was conducted in a rural district of West-Pomeranian province, in the primary health care center, where 279 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…This finding agrees with a study report from Egypt where 78.6% of the study participants did not adhere to self-blood glucose monitoring ( 53 ). However, this finding does not agree with findings from Saudi Arabia (29.2%) ( 56 ), Poland (40%) ( 57 ) and Oman (64.7%) ( 58 ). Despite the increasing level of diabetic cases, advancement in technology and medicine, glycemic level controlling has been insignificant in most diabetic patients in developing countries such as Ethiopia due to glucometer unaffordability and knowledge gaps.…”
Section: Discussioncontrasting
confidence: 79%
“…This finding agrees with a study report from Egypt where 78.6% of the study participants did not adhere to self-blood glucose monitoring ( 53 ). However, this finding does not agree with findings from Saudi Arabia (29.2%) ( 56 ), Poland (40%) ( 57 ) and Oman (64.7%) ( 58 ). Despite the increasing level of diabetic cases, advancement in technology and medicine, glycemic level controlling has been insignificant in most diabetic patients in developing countries such as Ethiopia due to glucometer unaffordability and knowledge gaps.…”
Section: Discussioncontrasting
confidence: 79%
“…Nearly three quarters of the studied sample performed selfmonitoring of their blood glucose, another study reported that only 40% of patients did so (18). Self-management skills could improve with longer duration of the disease.…”
Section: Discussionmentioning
confidence: 90%
“…The studies that have been conducted concern the assessment of only selected variables which play a role in disease management, such as self-monitoring of blood glucose, blood pressure and foot self-care. 28,29 The Polish adaptation of the SCODI may increase the research area in the evaluation of self-care in patients living with diabetes. This is significant due to the fact that a lack of systematic self-care assessment may contribute to a passive attitude in patients and thus cause low effectiveness of disease management.…”
Section: Discussionmentioning
confidence: 99%